Internal energy control of a cascaded H-Bridge Energy Router - Okunola, Abdullah Akolade (2024)
Energy efficiency is an important requirement in industry. Across several industrial applications, it is desired that maximum output is achieved for a given energy input. At material processing sites, several energy-intensive processes that are powered individually from generators run in various sequences, but the minimum amount of energy should be used. Power electronic converters can be used to improve energy efficiency at such sites by energising these processes from a single AC power supply source to minimise inefficiency.